Executive and memory dysfunction related to binge drinking in stroke survivors during a 9-year follow-up - Laari, Siiri; Kauranen, Tatu; Turunen, Katri; Mustanoja, Satu; Tatlisumak, Turgut; Poutiainen, Erja (Frontiers in Aging Neuroscience, 2024)
Background Ischemic stroke and heavy alcohol consumption are both known risk factors for cognitive impairment. The issue gains importance because the prevalence of stroke and binge drinking have both increased among working-aged adults. Alarmingly, a recent cross-sectional study suggests the additive negative effects of binge drinking and comorbid brain disease on cognition. However, the long-term cognitive prognosis of the additive effects of stroke and binge drinking on adults remains unknown. Methods In this prospective, two-center cohort study, we recruited consecutive 18–65-year-old patients with first-ever ischemic stroke along with demographically matched stroke-free controls. Patients participated in neuropsychological assessment at 6 months, 2 years, and 9 years after stroke, and in neurological assessment at acute care and at 9-year follow-up. Controls participated in a similar follow-up procedure. We examined the association between binge drinking, follow-up time, and long-term cognitive outcomes using repeated-measures analysis of variance. Results We included 85 patients who had had their first-ever and only ischemic stroke (mean age 53 years at the incident stroke). Patients were divided into binge-drinking (n = 22) and non-binge-drinking groups (n = 63) based on the shortened version of the Alcohol Use Disorders Identification Test. Follow-up data in healthy controls (n = 31) was used to normalize the patients' test scores for effects of age, sex, and education. We compared cognitive changes between binge-drinking and non-binge-drinking patients over a 9-year follow-up. Non-binge-drinking patients outperformed binge-drinking patients across all follow-up points on most of the executive function tests and in one memory test: binge drinking had a significant main effect both on executive function (the phonemic fluency task, p = 0.002; the Trail Making Test, p = 0.013) and memory (the list learning task, p = 0.002). Conclusion Binge drinking was associated with executive and memory dysfunction at three time points over a decade after a first-ever ischemic stroke. Subdiagnostic binge drinking might increase the adverse effects of a first-ever ischemic stroke on executive function and memory, evident over a decade poststroke.